Women and Islam, theoretical issues and current affairs - Sicilia Lorenzo, Raquel Elena Sicilia Lorenzo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Analyzing religion from a gender perspective allows us to understand the interaction between religious norms and power relations. Various studies have shown that religion has been used both to perpetuate patriarchy and to promote social change. In this context, feminist positions have been developed within different religious denominations, especially in the field of monotheistic religions. However, Western feminism has tended to confront the religious, making invisible the contributions of feminists within their own spiritual traditions. Development:The relationship between feminism and religion has been the subject of debates framed by ideological tensions and ethnocentric positions. While feminism in the Global North has promoted secularization as a path towards gender equality, many Muslim women have developed their own feminism within religious frameworks. Islamic feminism, which emerged at the end of the 19th century and consolidated in the 20th century, seeks to reinterpret sacred texts from a hermeneutic of suspicion. Authors such as Amina Wadud and Asma Barlas have demonstrated that the oppression of women does not come from the Koran, but from patriarchal interpretations. Despite their diversity, Islamic feminists agree on the need to reformulate religious norms to guarantee gender justice. Conclusion: Islamic feminism challenges traditional views of secular feminism and patriarchal Islam. While it faces criticism both within and outside Muslim communities, its approach broadens the perspectives of the struggle for gender equality. The reinterpretation of sacred texts from a feminist perspective becomes a key tool for social transformation and the vindication of women’s rights within Islam.